Karl Marx and Contradictions of "Capitalism 4.0" - Prodanov, Hristo (Research Papers, 2018)
Technologies are part of the logic of development of capitalism, and technological revolutions are an instrument for moving it from one stage to another. The aim of this research is to study the contradictions of the “Capitalism 4.0, based on the technologies of the Fourth industrial revolution. The research includes two main parts: The first one is related with the ideas of Karl Marx about the role of technologies in the development of capitalism and its stages, connected with different technologies. The second one is about the contradictions of “Capitalism 4.0”, connected with the technologies of the Fourth industrial revolution.